Predictive value of gamma globulin gap in evaluation of therapeutic response in multiple myeloma at Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: The current lack of a reliable, inexpensive tool to predict treatment response in newly diagnosed Multiple Myeloma (MM) patients poses an urgent need, especially in resource-limited countries. Gamma Gap (GG) represents the measured difference between serum total protein and albumin on conventional chemistry panel.Methods: We prospectively studied 53 newly diagnosed MM patients, who were admitted to the Cancer Treatment Center in Tishreen University Hospital in Latakia between July 2019 and July 2021, in order to determine the value of GG in predicting treatment response after first-line therapy.Results: There was a strong linear correlation between GG and M-spike at diagnosis, at midpoint, and after treatment with r:0.89, 0.91, and 0.85, respectively, and p